The teaching of Sciences and the Youth and Adults Education: a report about pedagogical practice of a teacher (Research, Society and Development, 2020)
Youth and Adult Education (EJA) is a basic education modality indicated to individuals who for some reason had your right denied to access formal education. Among the main demands of EJA, several studies highlight the proper training of teachers. To broaden the discussions about teacher training on Natural Sciences field, this work aimed to analyze the pedagogical practice of a science teacher of the youth and adults education modality from a state public school, also seeking to identify her conception of EJA, as well as their methodological references. Aiming to broaden the discussions about the training of teachers in Natural Science field, this experience report the observation and analyze the pedagogical practice of a Natural Science teacher, as well theirs conception of EJA and theirs methodological references used in his classes. Data collection was carried out using notes book during class observation, an interview with teacher and analysis of his teaching plan. In the document analysis was verified the need to establish a more detailed profile of the Natural Science teacher that act in EJA to drive pedagogical strategies that should from the reality where students are inserted. Furthermore, the experience reported proposes to the EJA teacher to use methodologies and didactic materials adapted properly to the reality of students, understanding them as subjects with previous knowledge non-formalized.